Computer aided-design of a gearbox/geartrains / Khairil Anuar Hashim and Roslan Abd. Mutalib - Hashim, Khairil Anuar; Abd. Mutalib, Roslan (1990)
This report describes an interative computer program that can be used in the design of the gearbox using spur gears. The program considers gear design parameter as recommended by American Gear Manufacturers ( AGMA ) which are described in the text by Shigley. Subroutines were used extensively to produced a modular and thus a portable program. The coding of the program was done in FORTRAN.